2017
DOI: 10.1523/jneurosci.1151-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Intellectual Disability and Schizophrenia Associated Transcription Factor TCF4 Is Regulated by Neuronal Activity and Protein Kinase A

Abstract: Transcription factor 4 (TCF4 also known as ITF2 or E2-2) is a basic helix-loop-helix (bHLH) protein associated with Pitt-Hopkins syndrome, intellectual disability, and schizophrenia (SCZ). Here, we show that TCF4-dependent transcription in cortical neurons cultured from embryonic rats of both sexes is induced by neuronal activity via soluble adenylyl cyclase and protein kinase A (PKA) signaling. PKA phosphorylates TCF4 directly and a PKA phosphorylation site in TCF4 is necessary for its transcriptional activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 73 publications
0
70
0
Order By: Relevance
“…Different TCF4 transcripts encode for various TCF4 protein isoforms (Fig. 1 B) that vary in their function and transactivation capability 4 , 8 . The major TCF4 transcripts comprising of 5′ exons 3b, 3c and 3d encode for isoform TCF4-B when spliced to internal exon 3; transcripts with exons 3b and 3d encode for isoform TCF4-C when spliced to exon 4; transcripts with exons 8a, 8bII and 8cII encode for isoform TCF4-D when spliced to exon 8; transcripts with exons 10a, 10b and 10c spliced to exon 10 encode for isoforms TCF4-A, TCF4-I and TCF4-H, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different TCF4 transcripts encode for various TCF4 protein isoforms (Fig. 1 B) that vary in their function and transactivation capability 4 , 8 . The major TCF4 transcripts comprising of 5′ exons 3b, 3c and 3d encode for isoform TCF4-B when spliced to internal exon 3; transcripts with exons 3b and 3d encode for isoform TCF4-C when spliced to exon 4; transcripts with exons 8a, 8bII and 8cII encode for isoform TCF4-D when spliced to exon 8; transcripts with exons 10a, 10b and 10c spliced to exon 10 encode for isoforms TCF4-A, TCF4-I and TCF4-H, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that TCF4 protein isoforms can be divided into longer and shorter isoforms which vary in their function and transactivation capability 4 , 8 . Currently FECD research focuses mainly on the CTG TNR and missplicing of longer TCF4 transcripts in FECD 17 , and little research has been done to analyze the expression of all the TCF4 transcripts in FECD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCF4 regulates many important functions during cortical development including neural progenitor proliferation, lineage commitment, neuronal migration, columnar organization, neurite outgrowth and myelination ( Li et al, 2019 ; Page et al, 2018 ; Phan et al, 2020 ). In addition, TCF4 appears to be an activity-dependent transcription factor that is capable of responding to neuronal activity while also regulating neuronal activity ( Page et al, 2018 ; Rannals et al, 2016 ; Sepp et al, 2017 ).…”
Section: Resource Detailsmentioning
confidence: 99%
“…88 Within purview of the fact that defects in myelination is a pathological marker of schizophrenia, this is interesting because two rare mutations (G428V and P299S) found in TCF4 that were associated with schizophrenia have been found to have increased transcriptional activity of TCF4 and in another study, density of mature oligodendrocytes essential for myelination have been observed to be reduced in white matter derived from prefrontal cortex of schizophrenia patients, which is an expected outcome if TCF4, a negative modulator of mature oligodendrocytes were to be overexpressed. [90][91][92] Also, treatment with DRD2/DRD3 agonist, quinpirole, has shown a decrease in the number of mature oligodendrocytes while treatment with haloperidol, a DRD2 antagonist, has shown an increase in the number of mature oligodendrocytes. 93 Many studies have noted this interplay of myelination and dopaminergic systems.…”
Section: Figure 5 Cinnarizine and Its Targets In The Schizophrenia Imentioning
confidence: 99%